The dialect of modernism : race, language, and twentieth-century literature - North, Michael, 1951- (Race and American culture., 1994)
The Dialect of Modernism uncovers the crucial role of racial masquerade and linguistic imitation in the emergence of literary modernism. Rebelling against the standard language and literature written in it, modernists such as Joseph Conrad, Gertrude Stein, T.S. Eliot, Ezra Pound, and William Carlos Williams reimagined themselves as racial aliens and mimicked the strategies of dialect speakers in their work. In doing so, they made possible the most radical representational strategies of modern literature, which emerged from their attack on the privilege of standard language.